Epidemic hypochlorhydria. Issue 6479 (11th May 1985) - Gledhill, T; Leicester, R J; Addis, B; Lightfoot, N; Barnard, J; Viney, N; Darkin, D; Hunt, R H
Abstract : During a study of gastric secretion four out of six previously healthy subjects developed hypochlorhydria after a transient illness with nausea, vomiting, and abdominal pain. Mean basal and peak acid outputs were 0 and 2.3 mmol (84 mg)/h one month after the onset of illness and 1.5 and 27.0 mmol/h (55 and 984 mg/h) at eight months' follow up. Two of the subjects were followed up at 18 months, when mean basal and peak acid outputs were 3.9 and 33.5 mmol/h (142 and 1221 mg/h). No endoscopic abnormality was seen at one and eight months, but biopsies showed active superficial gastritis, which resolved in one subject and became chronic in two. Schilling tests performed in three subjects at eight months showed diminished retention of vitamin B12. During hypochlorhydria a 24 hour intragastric analysis was performed for total and nitrate reducing bacteria, pH, and concentrations of nitrite and total and stable N-nitroso compounds. Of the 48 samples of gastric juice examined, 47 had bacterial growth of more than 10(6) organisms/ml and 46 had growth of nitrate reducing bacteria of more than 10(5) organisms/ml. Mean intragastric nitrite concentrations were 10 times higher than in a group of eight healthy controls. Both mean total and mean stable N-nitroso compound concentrations, however, were not appreciably different from those in controls. Although community transmission was a possibility, serological screening and electron microscopy of gastric biopsy specimens failed to show an infective cause. Transmission of an unidentified enteric pathogen via a contaminated pH electrode was therefore suspected. Thus gastric juice should not be returned to the stomach after contact with a contaminated glass electrode as this is a possible cause of atrophic gastritis.